LECTURA COMPRENSIVA COMO ESTRATEGIA DE APRENDIZAJE DEL IDIOMA INGLES DE LOS ESTUDIANTES DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA “QUEVEDO - Pineda Burgos, Raúl Fernando (2024)
The establishment of English as an international language has been accelerated by the catalytic effect of global communication and the high technology applied to it. This, in turn, is driven by two factors: the need for a common language and the ease of its dissemination. The reason for this growth lies in the fact that in many countries, English has been made a compulsory subject in official educational programs from primary school through university. This is the case in Chile, where English instruction was introduced in public primary schools. China is another example, where all students are required to learn English starting from the first grade as part of the country’s efforts to improve its competitiveness on various global stages. In Ecuador, since 2017, English instruction has been mandatory from the second year of schooling. However, the majority of students graduating from different educational institutions do not satisfactorily develop communicative competencies in the language, due, among other things, to the superficial approach to its teaching, which inevitably leads to a deficient development of such competencies among students. This analysis, beyond highlighting the importance of English and reading comprehension as a learning strategy for the language, seeks to call upon the relevant educational authorities, teachers, parents, and the student community in general to give the teaching of English the priority it requires as part of the current educational system and to improve the conditions for its instruction.